Eating Patterns of Elite Adolescent Athletes: Results of a Cross-Sectional Study of 51 Olympic Sports - Diehl, Katharina; Yarmoliuk, T.; Mayer, J.; Zipfel, Stephan; Schnell, A.; Thiel, A.; Schneider, S. (Deutsche Zeitschrift für Sportmedizin, 2013)
Purpose: Performance of elite sports can increase adolescents' energy and nutritional requirements. Therefore, the knowledge of daily eating habits is important to adequately support elite adolescent athletes in their nutrition. Methods: Based on data of German elite adolescent athletes in 51 Olympic sports (GOAL Study; n=1,138, 56.1% male; mean=16.33 years), we analyzed associations between the daily consumption of foods and athletes' characteristics. In addition, we compared the daily food consumption of elite athletes with that of non-elite athletes. Results: We found types of sport and nutrition-specific variables (e.g., getting information from nutritionists, having a nutrition plan, place of food intake) to be correlated with daily food intake. Compared to non-elite athletes, elite athletes had a significantly higher daily consumption of vitamin and fiber-rich products (47.9% vs. 43.2%), animal products (27.7% vs. 19.6%) and sweets (19.6% vs. 1.0%). Discussion: As only a quarter of the elite athletes were found to have gotten information from a nutritionist, and since nutritional education and counseling were shown to be important for healthy food choices in this group, offering information and education is absolutely essential. This applies especially for athletes in lower squads. However, their parents and coaches should also be educated in terms of nutrition.
CRIS-Team Scopus Importer:2021-12-06
Keywords: Eating behavior; Food frequency; Health behavior; Physical activity; Professional sports